PENGARUH RETURN ON ASSET, NET PROFIT MARGIN, DEBT TO EQUITY RQTIO DAN SIZE TERHADAP PERATAAN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016) - Wahyuni Dwi Asmara (Universitas Islam Malang, 2017)
This research was aimed to know effect simultaneously as well as partially ReturOn Asset, Net Profit Margin, Debt to Equity and Firm size on flattening profit. Population used in this research was that all manufacture companies which was registered in Bursa Efek Indonesia (BEI) in 2013-2016. Sample selection used purposive sampling. Based on criteria, it was obtained 45 companies that became sample in this research. The method that was used in the research used linear logistic regression. Based on analysis result could be told some conclusion such as: 1) Retur On Asset, Net Profit Margin, Debt to Equity Ratio and Firm Size had significant influence on flattening profit simultaneously 2) Net Profit Margin had positive and significant influence toward flattening profit, while Retur On Aset, Debt to Equity Ratio and Firm Size did not have significant influence to flattening profit.